Psychosocial Predictors of Emergency Management Behaviour for Non-Communicable Disease Emergencies Among Rural Community Adults in Thailand - Sukontip Arunmonlaphat; Yupayong Paha; Pacharamon Soncharoen (International Journal of Environmental Research and Public Health, 2026)
Background: Non-communicable disease (NCD) emergencies, including hypoglycaemia, stroke, acute coronary syndrome, and hypertensive crisis, call for prompt action by households and communities. The psychosocial mechanisms associated with emergency management behavior in rural Thailand, however, are not well understood. Objectives: The study pursued three objectives. It described levels of NCD emergency management behavior and the characteristics of emergency events reported during the preceding six months. It examined associations linking knowledge, Health Belief Model (HBM) constructs, social support, participation, self-efficacy, and emergency management behavior. Then, it identified the constructs with the strongest relations to behavior, along with an indirect pathway operating through self-efficacy, via structural equation modelling. Methods: A cross-sectional study analyzed data from 1321 community adults in Sisaket Province, Thailand, drawn from an initial 1407 records after excluding 86 with age below 21 years, incomplete data on SEM variables, or invalid disease-status coding. A structured, interviewer-administered questionnaire measured knowledge of NCD emergencies, HBM constructs, social support, family and community participation, self-efficacy, and emergency management behavior. Covariance-based SEM with item parcels and maximum-likelihood estimation was conducted; knowledge was treated as an observed variable. Results: Mean age was 58.0 years (SD = 14.3); 15.5% reported a recent emergency event. Knowledge was moderate-to-low (mean = 5.79/10; KR-20 = 0.440). Model fit was acceptable (CFI = 0.980; RMSEA = 0.047; SRMR = 0.049). Discriminant validity was supported by the Fornell–Larcker criterion for all constructs. Participation was strongly associated with self-efficacy (β = 0.858) and with emergency management behavior (β = 0.433); self-efficacy was also associated with emergency management behavior (β = 0.354). Participation had the largest total effect on behavior (0.737), combining a direct effect (0.433) and an indirect, self-efficacy-related effect (0.304). All structural-path variance inflation factors (VIF) were below 5.0 except participation behavior (VIF = 6.19), which remained below the more permissive threshold of 10.0. Conclusions: NCD emergency management behavior in this rural community was most strongly associated with family and community participation and with self-efficacy. Because the design was cross-sectional, these findings indicate association rather than confirmed causal or mediating pathways. Programmes should combine scenario-based knowledge with participatory practice, family role preparation, rehearsal of emergency-service (1669) activation, and confidence-building activities.